2009
DOI: 10.1080/13668250802688306
|View full text |Cite
|
Sign up to set email alerts
|

Research ethics and the use of visual images in research with people with intellectual disability

Abstract: The aim of this paper is to encourage debate about the use of creative visual approaches in intellectual disability research and discussion about Internet publication of photographs. Image-based research with people with intellectual disability is explored within the contexts of tighter ethical regulation of social research, increased interest in the use of visual methodologies, and rapid escalation in the numbers of digital images posted on the World Wide Web. Concern is raised about the possibility that tigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 39 publications
1
87
0
6
Order By: Relevance
“…In all cases, this approach involved contacting both the person with intellectual disabilities and a support person to request that they provide consent together. A study by Boxall and Ralph (2009) supported these findings and indicated that service providers or other individuals with whom people with intellectual disabilities may be more familiar may be the most suitable people from whom to acquire satisfactory agreement. To ensure that the content of the research information is understood, it may also be beneficial to repeat the information several times and in different ways (Kittelsaa, 2010;Wennberg and Kjellberg, 2010), as in the author's study.…”
Section: Voluntary Informed Consentsupporting
confidence: 54%
“…In all cases, this approach involved contacting both the person with intellectual disabilities and a support person to request that they provide consent together. A study by Boxall and Ralph (2009) supported these findings and indicated that service providers or other individuals with whom people with intellectual disabilities may be more familiar may be the most suitable people from whom to acquire satisfactory agreement. To ensure that the content of the research information is understood, it may also be beneficial to repeat the information several times and in different ways (Kittelsaa, 2010;Wennberg and Kjellberg, 2010), as in the author's study.…”
Section: Voluntary Informed Consentsupporting
confidence: 54%
“…This will be freely available online and will hopefully result in wider exposure to potential participants, as people with ID increasingly have access to health information through access to DVDs (Boyden et al . 2009), the Internet (Boxall & Ralph 2009) and other multimedia sources. Although we were satisfied with our chosen framework for assessing capacity, for a future study we will more rigorously document our assessment conversations with participants. Analysis of such material post hoc could highlight subtle but important strengths or weaknesses in a person's ability to understand or use the information.…”
Section: Discussionmentioning
confidence: 99%
“…As the international research community works to correct the past abuses of research participants, concerns have emerged that a protectionist mind set has taken hold, contributing to more conservative practice and posing new challenges for researchers working with people with learning disabilities (Iacono 2003(Iacono , 2006Boxall and Ralph 2009;. Grove (2002Grove ( , 2004 argues that deciding not to research with individuals who are deemed 'vulnerable' may actually increase their vulnerability because people will remain ignorant of their circumstances and treatment.…”
Section: Background and Contextmentioning
confidence: 99%
“…There are concerns that adults with learning disabilities may be needlessly excluded from research (Iacono, 2006;Lai et al, 2012) or at a greater risk of being subjected to harmful research (McDonald and Kidney, 2012). People with high support needs may be at particular risk of research exclusion due to concerns about demonstrating informed consent (Ledger, 2012) and difficulties in obtaining ethical approval for inclusive methodologies (Boxall and Ralph, 2009;.…”
Section: Recruitment Of Intervieweesmentioning
confidence: 99%